Perspectives of Artificial Intelligence (AI) in the Global South: A Bibliometric Study - Awasthi, Shipra; Das, Suman; Das, Anup Kumar; Tripathi, Manorama (Journal of Data Science, Informetrics, and Citation Studies, 2026)
Artificial Intelligence has gained momentum over a period of time. Its rise poses a great threat to society in various regions. The study aims to focus on the current trends, important themes, and the challenges encountered by the researchers. It also underlines the laws and regulations enacted by the government to control deepfakes as they may endanger the safety of society. The present study conducted a bibliometric study comprising 3,285 articles, adopting R Software and VOSViewer for the analysis. The findings of the study revealed that the USA, UK and China are publishing significantly on AI; Pennycook G is the leading author; and ‘fake news,’ ‘social media,’ and ‘disinformation’ are the major keywords in the published literature. The study is significant for researchers to understand the trends and themes dealt with in the published articles. The study also provides an overview of the highly cited articles in the area of artificial intelligence.
Keywords: AI; Artificial intelligence; Bibliometrics; Developing Nations Global South; informetric; Technology